Using geospatial technology to teach language and content to English learners. Issue 2 (7th December 2018) - Kangas, Sara E. N.; Hammond, Thomas C.; Bodzin, Alec M.
Abstract : It has been well documented that English learners (ELs) in U.S. secondary schools have limited access to rigorous content area curriculum, in particular science. Yet watering down or forgoing content area instruction compromises the short‐ and long‐term academic trajectories of ELs. Thus, the need for science curricula that marries rich learning opportunities with language support continues to be a pressing need in EL education. This article draws on an innovative inquiry‐based science curriculum to demonstrate how geospatial technologies can be utilized to provide ELs with rigorous academic and second language learning opportunities. The featured curriculum includes tasks that engage students in locally relevant issues and draws on principles of second language acquisition and geospatial learning. The curriculum ultimately demonstrates how opportunities to learn can be cultivated for ELs as well as other language learners in a wide range of academic contexts.